The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1002/sdtp.13965
|View full text |Cite
|
Sign up to set email alerts
|

48‐2: Design Strategies of Fluorescent Dopants toward Pure Blue for Highly Efficient Top Emission OLEDs

Abstract: A blue dopant (BD) emitting pure blue fluorescence was created on new design strategies that combined specific partial molecular structures to reduce peak shoulder of the fluorescence spectrum. The top emission organic light emitting diode using the new BD achieved L/J/CIEy=201, which was about 10% higher than the conventional BD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
(6 reference statements)
0
7
0
Order By: Relevance
“…In SID 2020, we reported that the TE device with our BD material with narrow emission band shows high performance in terms of efficiency 18 . In this paper, the TE device of bilayer EML was fabricated using the narrow‐band BD and compared with that of the monolayer EML.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…In SID 2020, we reported that the TE device with our BD material with narrow emission band shows high performance in terms of efficiency 18 . In this paper, the TE device of bilayer EML was fabricated using the narrow‐band BD and compared with that of the monolayer EML.…”
Section: Resultsmentioning
confidence: 98%
“…In SID 2020, we reported that the TE device with our BD material with narrow emission band shows high performance in terms of efficiency. 18 In this paper, the TE device of bilayer EML was fabricated using the narrowband BD and compared with that of the monolayer EML. As a result, the improvement effect on efficiency and lifetime was confirmed even in TE device, and blue index (BI) = 259 and LT95 = 198 h were achieved (Table 6 and Figure 9).…”
Section: Application To Te Devicementioning
confidence: 99%
See 1 more Smart Citation
“…In SID 2020, we reported that the top emission (TE) device with our BD material with narrow emission band shows high performance in terms of efficiency [8]. In this paper, the top emission device of bilayer EML was fabricated using the narrowband BD and compared with that of the monolayer EML.…”
Section: -3 Application To Top Emission Devicementioning
confidence: 99%
“…In recent years, the time at which the luminance is reduced by 3 (LT97) or 5 (LT95) from the initial luminance is often used as an indicator of device lifetime that considers display burn-in [1]. A long-life device with an LT95 of approximately 300 h when driven at a constant current density of 50 mA/cm 2 at room temperature has been achieved [2] by, for example, improving the emission layer (EmL) material in a blue fluorescent device. However, a significant luminance decrease that occurs during the initial driving stage, i.e., initial degradation, inhibits further improvements in the LT95.…”
Section: Introductionmentioning
confidence: 99%